Program Tol Laut pada Pengiriman Logistik di Wilayah Sulawesi Tenggara - Awaluddin Awaluddin; Danny Setiawan (Institut Transportasi dan Logistik Trisakti, 2022)
This study aims to determine the impact of the implementation of the sea toll program in providing logistics in Southeast Sulawesi Province. The data collection method was carried out through field surveys and questionnaires. The technique of determining respondents uses purposive sampling techniques. The data analysis method uses the Analytical Hierarchy Process (AHP) method. The results show that the consistency of the government in policies and determining the port of sea toll ships resulted so that the return cargo activities of commodities or local agricultural and marine products still used expeditionary shipping, and socialization to the community was not maximized to utilize marine toll program. From the analysis, it is concluded that the maritime highway program is very effective with a weight of 0.287823083. Strategies that must be prioritized in supporting effectiveness are cost factors and route factors with sub-factors; container subsidies, handling fees, shipping frequency, and travel time.